Isolation of a Previously Unidentified Polysaccharide (MAR-10)from Hyssop officinalis That Exhibits Strong Activity Against Human Immunodeficiency Virus Type 1 - Gollapudi, S.; Sharma, H.A.; Aggarwal, S.; Byers, L.D.; Ensley, H.E.; Gupta, S.
A polysaccharide (MAR-10)was isolated from the aqueous extract of the plant Hyssop officinalis and examined for its activity against HIV-1 (SF strain)in HUT78 T cell line and primary cultures of peripheral blood mononuclear cells. MAR-10, in a concentration-dependent manner,inhibited HIV-1 replication as demonstrated by the inhibition of HIV-1 p24 antigen and syncytia formation. Furthermore, MAR-10 had no significant direct toxicity or effect on lymphocyte functions or CD4+ and CD8+ T cell counts. In addition, MAR-10 has broad spectrum anti-glycosidase activity. Our study demonstrates that MAR-10 contains strong anti-HIV-1 activity that may be useful in the treatment of patients with HIV-1 infection.